Diabetic Muscle Infarction: Resolution of Rare Microangiopathy with Over-The-Counter Medication. (14th July 2021) - Jariwal, Roopam; Raza, Nadia; Cadang, Catherine; Rahman, Syed; Contreras, David; Sidhu, Ramanjeet; Bhandohal, Janpreet
Abstract : Diabetic muscle infarction (DMI) is a rare complication of poorly controlled type 1 and type 2 diabetes seen mostly in those who have already experienced microvascular complications. Currently, the incidence and prevalence of DMI are difficult to conclude, and there is no clear algorithm or standard of care in managing this condition. Pathogenesis of the microangiopathy of DMI remains unclear. A major finding in this investigation of DMI emphasizes that, within 2–17 weeks, patients who initiate low-dose acetylsalicylic acid, bed rest, and close outpatient follow-up see significant size reduction of lower extremity mass and complete resolution of pain without being subjected to invasive muscle biopsy.